Characteristics of Edamame Soygurt with Stevia Sweetener as a Functional Food for Diabetes Mellitus Patients - Lirista Dyah Ayu Oktafiani; Vadira Rahma Sari; Septi Nur Rachmawati; Farida Wahyu Ningtyias; Cindy Yunita Sari (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2026)
Type 2 Diabetes Mellitus is a metabolic disorder characterized by increased blood sugar (hyperglycemia) due to decreased insulin secretion. Stevia can be an alternative for people with diabetes mellitus. The addition of stevia sweetener is beneficial because it has a very low calorie content, making it safe for people with diabetes. This study aimed to determine the isoflavone content, physical properties, and sensory characteristics of edamame soygurt containing stevia as a functional sweetener. This study used 5 formulations of sucrose and stevia levels in sequence: 100:0 (F0), 75:25 (F1), 50:50 (F2), 25:75 (F3), and 0:100 (F4). All formulas were tested for isoflavone contents, physical properties (pH and viscosity), and sensory characteristics (hedonic test). The test for differences in isoflavone and pH levels between formulations was carried out using ANOVA. In contrast, the sensory properties test data were analyzed using the Friedman test at the 5% significance level. F0 showed the highest isoflavone content (12.55), the most acidic pH was in the F0 formulation (4.56), and the highest viscosity was in the F4 formulation (0.98). Sensory tests were conducted on aspects of color, aroma, taste, texture, overall, and the best formulation. The hedonic test showed no significant difference in the element of color among the formulas (p > 0.05). On the other hand, aroma, taste, texture, and overall aspects showed significant differences in several formulations (p < 0.05). The results of the best formulation test based on panelist perceptions showed that F4 was the most preferred formulation among the majority of panelists.